BATCH AND FLOW-INJECTION SPECTROPHOTOMETRIC METHODS FOR DETERMINATION OF PARACETAMOL IN PHARMACEUTICAL PREPARATIONS BY COUPLING WITH DIAZOTIZED 4-NITROANILINE - Al-Abachi, Mouayed; Sinan, Raghad; Falah, Zaineb (Iraqi Journal of Science, 2024)
Two sensitive and fast spectrophotometric methods using batch and flow-injection procedures for the determination of paracetamol are proposed. The methods are based on the formation of a red dye between this drug and diazotized 4-nitroaniline in sodium carbonate medium. The reaction conditions are studied and optimized for both batch and flow injection procedures. The calibration graphs resulting from measuring the absorbance at 528 nm are linear over the ranges 0.5 – 20 and 1 – 150 μg mL-1 of paracetamol with relative standard deviations of 1.2420% and 1.5634% for batch and flow-injection methods, respectively. The methods are applied to the routine analysis of paracetamol in pharmaceutical preparations. The obtained results agree with those obtained by the British Pharmacopoeia method.Keywords: Spectrophotometric; Flow-injection; Paracetamol; Diazotized 4-nitroaniline; Pharmaceutical preparations.